Near-Infrared Dual-Emission Quantum Dots–Gold Nanoclusters Nanohybrid via Co-Template Synthesis for Ratiometric Fluorescent Detection and Bioimaging of Ascorbic Acid In Vitro and In Vivo - Zhao, Peng; He, Kaiyu; Han, Yitao; Zhang, Zhen; Yu, Mengze; Wang, Honghui; Huang, Yan; Nie, Zhou; Yao, Shouzhuo (Analytical chemistry (Washington), 2015)
Near-infrared (NIR) quantum dots (QDs) have emerged as an attractive bioimaging toolkit for exploring biological events because they can provide deep imaging penetration and low fluorescence background. However, the quantitation process of such NIR QDs generally relies on single-emission intensity change, which is susceptible to a variety of environmental factors. Herein, for the first time, we proposed a protein-directed co-template strategy to synthesize a NIR-based, dual-emission fluorescent nanohybrid (DEFN) constructed from far-red gold nanoclusters and NIR PbS QDs (AuNCs-PbS-QDs). The convenient protein-directed co-template synthesis avoids the tedious chemical coupling and modification required in conventional preparation approaches of DEFNs. Additionally, the dual-emission signals of AuNCs-PbS-QDs exhibit two well-resolved emission peaks (640 and 813 nm) separated by 173 nm, which can eliminate environmental interferences by the built-in correction of ratiometric signal, resulting in a more favorable system for bioimaging and biosensing. Next, the target-responsive capability of this NIR-based DEFN to ascorbic acid (AA) was discovered, enabling the proposed DEFN to ratiometrically detect AA with a linear range of 3–40 μM and a detection limit of 1.5 μM. This DEFN sensor possesses high selectivity, rapid response, and excellent photostability. Moreover, the feasibility of this NIR nanosensor has been fully proved by the ratiometric detection of AA for fruit internal quality assessment, in vitro cellular imaging, and in vivo imaging in nude mice.